Relationship between MCP1 (-2518A>G) gene variants and ovarian cancer in Turkish population - Attar, R.; Yilmaz, S. G.; í‡akmakoğlu, B.; Duman, S.; Yildirim, G.; Görmüş, U.; ć°sbir, T. (Cellular and Molecular Biology, 2017)
The monocyte chemoattractant protein-1 (MCP-1) gene polymorphism(-2518A>G) in the regulatory region of the MCP-1 protein has been reported to be associated with cancer risk. In this study we aimed to investigate the relationship of MCP-1 (-2518A>G) gene polymorphism and ovarian cancer. MCP-1 genotyping was performed using polymerase chain reaction from blood samples ofovarian cancer patient (n=56) and a control groups (n=52).There was a significant difference in MCP1 (-2518A>G) genotypes between the patient and control groups (p=0.049; x2=6.042). AA carriers were significantly higher in the control group (p=0.014) whereas AG genotype and G allele carriers were significantly higher in the ovarian cancer group (p=0.029, p=0.014, respectively). This study suggests that MCP-1 (-2518A>G) AG genotype and G allele could be considered as risk factor for susceptibility to ovarian cancer.